C-kit and bcl-2 Are Not Useful Markers in Differentiating Adenoid Cystic Carcinoma from Polymorphous Low-Grade Adenocarcinoma. (15th July 2011) - Meer, Shabnum; Singh, Sunita; Altini, Mario
Abstract : Aims . To evaluate the immunohistochemical expression of bcl-2 and c-kit proteins in the salivary gland tumors, adenoid cystic carcinoma, and polymorphous low-grade adenocarcinoma with a view to tumor differentiation. Methods . Immunohistochemical studies were performed on 29 adenoid cystic carcinoma and 23 polymorphous low-grade adenocarcinoma archival cases with bcl-2 and c-kit antibodies using standard procedures, and the data were statistically analyzed. Results . The difference in bcl-2 expression in adenoid cystic carcinoma and polymorphous low-grade adenocarcinoma was not statistically significant. Whilst the difference in c-kit expression was statistically significant (P = 0.01 ), the difference proved small so as to be of no practical or diagnostic importance. Moderate to strong immunostaining was noted in adenoid cystic carcinoma with c-kit, the pattern and intensity varying within different histological subtypes, being greater the more aggressive the tumor subtype. Conclusions . Bcl-2 and c-kit are not useful as immunohistochemical markers in differentiating adenoid cystic carcinoma from polymorphous low-grade adenocarcinoma.